The Role of Spectral Focused Imaging (SFI) in Diagnosing Subtle Mucosal Changes in Patients with Ulcerative Colitis - Andreea DOBROMIRESCU; Simona-Andreea BALOSU; Adrian DUMITRU; Lucian NEGREANU (Modern Medicine, 2024)
Background: Due to the rapid development of new diagnostic and therapeutic endoscopic techniques, there has been a gap between their development and implementation in daily practice, as well as in their uptake in guideline recommendations1. We investigated the effectiveness of spectral focused imaging (SFI), a new optical chromoendoscopy system (SonoScape, Shenzhen, China)2, in diagnosing subtle mucosal changes in patients with inactive ulcerative colitis. Materials and Methods: A group of 12 patients with quiescent ulcerative colitis were randomly assigned at a 1:1 ratio to undergo colonoscopy with high-definition white light (group A) or SFI (group B). The mucosal pattern, location of the mucosal changes (measured in centimeters from the anal verge), morphology, size and duration of the endoscopic procedure were recorded, while the disease activity was established following the Mayo endoscopic score for ulcerative colitis. Subsequent to the endoscopic characterization, targeted biopsies (or random biopsies in a case of normal colonic mucosa) were obtained from every segment for histopathological follow-up analysis. Results: The median endoscopic activity index, based on the Mayo ulcerative colitis endoscopic score, was 1 for both groups of patients. Taking into account the duration of the examination, the median value was 17.3 minutes in group A and 18.5 minutes in group B. Upon examining the concordance between the endoscopic prediction of disease activity and the histological findings, we obtained a 55% degree of conformity in group A, compared to 90% in group B. Conclusions: This pilot study showed that image-enhanced endoscopy using SFI might increase the rate of detection and demarcation for subtle inflammatory changes in the mucosa, correlating with potential histologic activity. Furthermore, this diagnostic tool could provide a more accurate and earlier identification of areas of minimal inflammation than conventional techniques.